Evaluasi Keragaman Morfologi dan Agronomi 7 Klon dan 2 Varietas Tanaman Tebu (Sacchaum officinarum L.) Keprasan Satu Di Kebun Ploso Klaten – Kediri - Muhammad Dimam Abror; Setyo Budi; Wiharyati Nur Lailiyah (Fakultas Pertanian, Universitas Warmadewa, 2023)
Sugarcane (Saccharum officinarum L.) as a raw material in the sugar production process is one of the basic needs of the Indonesian population. This research was conducted at the HGU Plantation C.11 Djengkol PG Islamic Boarding School, the new PT Perkebunan Nusantara X. Ploso Klaten District, Kediri Regency. This research was conducted from May to July 2023. This design used a one-factor randomized block design (RBD) of 9 treatments, consisting of 7 sugarcane clones and 2 sugarcane varieties consisting of K1 (Clone SB01 UMG.NX), K2 (Clone SB03 UMG.NX), K3 (Clone SB04 UMG.NX), K4 (Clone SB11 UMG.NX), K5 Clones (SB12 UMG.NX), K 6 (Clone SB19 UMG.NX), K7 (Clone SB20 UMG.NX), K8 (Variety PS862), K9 (Variety Bululawang). The parameters observed were growth variables (stem length, number of stems, number of leaves and diameter) and yield (brix). The analysis used was descriptive statistics, ANOVA followed by 5% DMRT follow-up test, correlation test, genetic diversity and heritability test. From the 5% DMRT results, there is a significant difference in the variables of plant height and diameter of the sugar cane plant. Clone SB12 UMG.NX had the best growth with a stem length of 257.33 cm, number of stems 8.33, number of leaves 8.22 and a diameter of 26.22 mm. There is no significant difference in the outcome variables. The highest Brix was obtained by the SB19 UMG clone. NX with a value of 27.00%.